Speeding, Punishment, and Recidivism: Evidence from a Regression Discontinuity Design - Markus Gehrsitz (Institute of Labor Economics (IZA), 2017)
This paper estimates the effects of temporary driver's license suspensions on driving behavior. A little known rule in the German traffic penalty catalogue maintains that drivers who commit a series of speeding transgressions within 365 days should have their license suspended for one month. My regression discontinuity design exploits the quasi-random assignment of license suspensions caused by the 365-days cut-off and shows that 1-month license suspensions lower the probability of recidivating within a year by 20 percent. This is largely a specific deterrence effect driven by the punishment itself and not by incapacitation, information asymmetries, or the threat of stiffer future penalties.
Keywords: I12; K42; R41; 330; crime; speeding; deterrence; regression discontinuity